Composição fitoquímica e potencial antimicrobiano dos óleos essencias de Alecrim-pimenta e Citronela - Ribeiro, Michel Douglas Santos (2021)
Essential oils (OE's) are composed of secondary metabolites and have a complex mixture of volatile substances, extracted from various parts of plants, usually medicinal. They have wide diversity and properties, including antibacterial, antifungal and antiviral. With the intensification of research on oil essences as candidates for natural additives, the present work aimed to investigate the phytochemical composition of essential oils of Rosemary-pimenta (Lippia sidoides Cham.) and Citronella (Cymbopogon nardus) seeking their Application and antimicrobial potential against pathogenic bacteria of food origin. The experiment was carried out at the Urban Agriculture Laboratory (LAU/UFC) and at the Technological Vocational Center (CVT/UFCG). After extracting the essential oils using the steam dragging method, gas chromatography analysis and phytochemical characterization were carried out. Then, in the Microbiology laboratory of the (CVT/UFCG) the tests were carried out using the diffusion method and wells to identify the potential of the antimicrobial activity and the susceptibility tests in the methods. The experimental design adopted was completely randomized (DIC) in a factorial scheme (3x3x3) with 4 replications and for the evaluation of synergism between oils (7x3) with 4 replications. Using the two-way PERNAMOVA test with 9,999 permutations, pairwise tested by the Mann-Whitney post-hoc test in R 4.0.2 and Past 4.06 software. The results allow us to conclude that the studied essential oils of Rosemary-pepper and Citronella can be widely used by the industry due to their repellent, antioxidant and antimicrobial properties. Especially when used pediatrically or in combination, they were efficient in strangling S. aureus.